Commonality in liquidity among Middle East and North Africa emerging stock markets: Does it really matter? - (:unkn) unknown (My University, 2019)
This study investigates commonality in daily liquidity among 11 emerging stock markets from the Middle East and North Africa from January 2005 to June 2017. First, we test long memory in liquidity in these markets. Second, we select a number of factors eligible to affect liquidity commonality among local, regional and global factors. We find that regional and US factors do not explain liquidity variations in all the markets that exhibit low sensitivity to external factors. Our results are robust to the use of alternative proxies. The analysis in sub-periods confirms our results showing that most markets are not very sensitive to fluctuations and external shocks of liquidity. For international investors, stock markets in the Middle East and North Africa present an opportunity for further diversification, as these markets exhibit weak correlations between them and with the global market with regard to liquidity.
Keywords: African Research